STATE OF JNK AND P38 MAP-KINASE SYSTEM IN BLOOD monon uclea r le ucocytes DUR ING INFLAMMATION - N. Y. Chasovskih; N. V. Ryazantseva; E. V. Kaigorodova; O. E. Chechina; E. G. Sokolovich; V. V. Novitskii (Медицинская иммунология, 2014)
Abstract. Pogrammed cell death of peripheral blood mononuclear leucocytes from patients with acute inflammatory diseases (non-nosocomial pneumonia, acute appendicitis) was investigated under ex vivo conditions, upon cultivation of the cells with selective inhibitors of JNK (SP600125) and р38 МАРК (ML3403). In vitro addition of SP600125 and ML3403 under oxidative stress conditions prevents increase of annexinpositive mononuclear cells numbers, thus suggesting JNK and р38 МАР-kinases to be involved into oxidative mechanisms of apoptosis deregulation. A role of JNK in IL-8 production by mononuclear leucocytes was revealed in cases of acute inflammation. Regulatory effect of JNK and p38 MAP-kinases can be mediated through activation of redox-sensitive apoptogenic signal transduction systems, as well as due to changes in cellular cytokine-producing function.